The Role of Code Switching in English Vocabulary Development: A Study of Eleventh Grade Students at SMAN 5 Palu - Afila, Lala; Jamiluddin, Jamiluddin; Patmasari, Andi; Mashuri, Mashuri (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to examine the role of code-switching in the development of English vocabulary among eleventh-grade students at SMAN 5 Palu. This research employed a descriptive quantitative approach. The population of this study consisted of all eleventh-grade students, with a sample of 30 students selected based on their involvement in English learning activities that applied code-switching. The data were collected through a Likert-scale questionnaire. Data analysis was conducted using SPSS, including validity testing, reliability testing, normality testing, and mean score analysis. The results of the validity test indicated that most questionnaire items were valid, while the reliability test showed a Cronbach’s Alpha value of 0.729, indicating that the instrument was reliable. The normality test using the Shapiro–Wilk method showed that the data were normally distributed. The mean score analysis revealed that students had positive perceptions of the use of code-switching in English vocabulary learning, particularly in helping them understand new vocabulary, reduce learning difficulties, and increase their confidence during the learning process. Based on these findings, it can be concluded that code-switching plays a positive role in supporting the English vocabulary development of eleventh-grade students at SMAN 5 Palu.